Gene Mutation Profile in Chronic Myelogenous Leukemia BCR-ABL. Positive Chronic Phase Patients Which not Response to lmatinib Treatment in Dr. Soetomo Teaching Hospital Surabaya lndonesia - Ugroseno Yudho Bintoro, Siprianus (The Korean Association of Internal Medicine, 2014)
To determine patterns of gene mutations in BCR-ABL tyrosine kinase in chronic myelogenous leukemia BCR-ABL positive chronic phase are not complete molecular response to lmatinib treatment methods: Gene Mutation Analysis has been done in sixteen chronic myelogenous leuki mia patients with BCR-ABL positive chronic phase who are not complete molecular response to lmatinib after 18 months treatment Result: We found C944T gene mutation in 9 (56,25%) patients, T1O52C gen mutation in 16 patient (100%), and T932C gene mutation in 13 patients (81,25%). One Type of Mutation found in one patient, two types of mutations in six patients, and three type mutations in nine patients